Όπερα Δωματίου : Στην Αλεξία - (:unkn) unknown (My University, 2022)
Βασισμένο στο βιβλίο "Τον Καιρό του Βουλγαροκτόνου" της Πηνελόπης Δέλτα το έργο "Στην Αλεξία" της Σοφίας Μπαρδούτσου.Είναι για οκτέτο οργάνων, χορωδία, παιδική χορωδία και σολίστ (τρείς πρωταγωνιστές και κάποιοι δευτερεύοντες ρόλοι). Στην προετοιμασία της χορωδίας και διεύθυνση η Σοφία Κετεντζιάν. Στην προετοιμασία της παιδικής χορωδίας η Αμαλία Μπελιά. Την σκηνοθεσία θα αναλάβει η ηθοποιός Ναταλία Καποδίστρια και στο πλαίσιο της παράστασης θα έχουμε μαζί της εβδομαδιαία θεατρικά εργαστήρια.

Based on the book "The Time of the Bulgarian Killer" by Penelope Delta, the play "In Alexia" by Sofia Bardoutsou. It is for octet of instruments, choir, children's choir and soloists (three protagonists and some secondary roles). In the preparation of the choir and conducted by Sofia Ketenjian. Amalia Belia in the preparation of the children's choir. The director will be the actress Natalia Kapodistria and as part of the show we will have weekly theater workshops with her.
Chamber Opera Work: Alexia
Keywords: Βουλγαροκτόνος, Μπαρδούτσου, Δέλτα, Χορωδία, Μαέστρος, Σολίστ, Σύνθεση; Composition, Modern, Bardoutsou,Fyssa,Soloist, Maestro, Orchestra, Choir